English Language Students’ Perception on the Use of Zoom Application toward Their Speaking Performance at University of Muhammadiyah Gresik - Alfiyah Rahman; Tri Yuli Ardiyansah; Noviatul Rochmah; Ulfatul Ma’rifah; Khoirul Anwar (Universitas Muhammadiyah Gresik, 2022)
Zoom Application is widely known as one of the most popular video conference applications used in online learning process during COVID-19 outbreak. Zoom application is considered as an interactive learning platform that enables students to interact with each other online. It provides lots of features for online learning that help students improve their speaking skill better. Therefore, this study specifically examined the perception of English students toward zoom application in online learning process. The research design used was a combined quantitative and qualitative to get more detailed information. The data collection used was in the form of questionnaire consisted of aspect of perception and speaking performance aspect. Unstructured interview in focus group discussion was used to support the result from questionnaire. The result showed that students had positive responses on their perception toward the use of Zoom application. Most of the students responded that Zoom application helped them perform speaking activity. The result of interview in focus group discussion also showed reasons that most students chose using Zoom for their speaking performance because it was easy to use and provided useful features for interaction with their teacher and other students. However, the main problem faced by students while using zoom application was internet connection. This gave bad effect for their learning process because they could not catch some of the material explained by the lecturer.